Students’ career choice preferable: a case study at Universiti Malaysia Kelantan / Siti Sarah Kamarudin - Kamarudin, Siti Sarah (2011)
The intense competition in seeking job nowadays has made university students especially undergraduate students need to have competitive advantage. The same goes to undergraduate students from Universiti Malaysia Kelantan. Hence, one way of improving competitive advantage is by enhancing their skill in term of entrepreneurship education that is believed can help them to build their career once they have graduated soon. Therefore, the aim of this study is to examine the level of students’ entrepreneurial intentions. This study has been conducted to determine the factors that influence students’ career choice preferable. This paper explores the impact of entrepreneurship education, individual attitude and family factor on the students’ career choice preferable and among 100 students drawn from Universiti Malaysia Kelantan (UMK) focusing on Entrepreneurship and Business Faculty. Two research questions and three hypotheses were raised for the study. The research in this study is based on questionnaire distributed to the 100 respondents who were from Faculty of Entrepreneurship and Business at UMK. The data collected were analyzed using frequency distribution analysis, regression analysis and hypothesis testing analysis. The findings in this study show that the factor that influence UMK students’ career choice to be entrepreneur are, individual attitude followed by entrepreneurship education and least important is family background factor